Crohn's disease in monozygotic twins. Issue 733 (November 1986) - Rampton, D. S.; Stott, R. B.
Abstract : A pair of monozygotic twins with Crohn's disease is described. Both have ileocaecal disease and suffered their first symptoms after living apart for 6 years. The pathogenic role of hereditary and environmental factors is discussed in the light of this and previous reports of twins with Crohn's disease.